Áp dụng tính chất của dãy tỉ số bằng nhau ta có:
\(\frac{ab+ac}{2}=\frac{ba+bc}{3}=\frac{ca+cb}{4}=\frac{\left(ab+ac\right)+\left(ba+bc\right)-\left(ca+cb\right)}{2+3-4}=\frac{2ab}{1}\)
Tương tự \(\frac{ab+ac}{2}=\frac{bc+ba}{3}=\frac{ca+cb}{4}=\frac{2bc}{5}\)
\(\frac{ab+ac}{2}=\frac{ba+bc}{3}=\frac{ca+cb}{4}=\frac{2ac}{3}\)
Do đó \(\frac{2ab}{1}=\frac{2bc}{5}\Rightarrow\frac{a}{1}=\frac{c}{5}\Rightarrow\frac{a}{3}=\frac{c}{15}\)
\(\frac{2bc}{5}=\frac{2ac}{3}\Rightarrow\frac{b}{5}=\frac{a}{3}\)
Do vậy \(\frac{a}{3}=\frac{b}{5}=\frac{c}{15}\)
Áp dụng tính chất của dãy tỉ số bằng nhau ta có:
Tương tự
Do đó
Do vậy